The Archetype of the Great Mother and Maternal Societies: The Code of Emotions and Affections - Di Nicola, Paola (Italian Sociological Review, 2026)
This article aims to analyse the social imaginary of the post-industrial society. Its starting point is Gilbert Durand’s concept of the social imaginary, supposedly far more influenced by the Nocturnal Order (with feminine connotations) than the Diurnal Order (predominantly masculine). The article suggests that the social imaginary which took shape in affluent societies in the 1960s and 1970s, partly as a result of widespread mechanisms of redistribution, was dominated by maternal symbols encouraging values of inclusion, equality, freedom, and self-fulfilment. With the transition to an increasingly technocratic and competitive society, these positive symbols slowly shifted towards an all-encompassing maternal form, creating dependency, passivity, a decline in civic engagement, and consumerism. This is a sign of the resurgence of the Nocturnal Order with its silent forms of social control, favoured by widespread forms of addiction and the drive for self-realisation in the consumer world.